Radon-222 in Drinking Water: Concentration and Radiological Risk in Nigerian Boreholes - Akeem, Adeyoju Adewale; Nnamdi, Agu Mathew; Israel Ndamawo, Gana; Yakubu, Shedrach (Indonesian Journal of Green Chemistry, 2025)
The consumption of contaminated water, especially those polluted by heavy metals, effluents, radioactive waste, etc., has posed a significant health risk in most developing economies. Therefore, researchers nowadays strive to ameliorate this menace. Hence, this study analyzed the concentration of Radon-222 in twenty drinking water samples collected from boreholes in Nigeria to provide insight into the concentration distribution of Radon-222 in the northwestern part of Nigeria. The Radon-222 concentrations in borehole water samples collected from Lagos and Ogun states were measured using a liquid scintillation counter at the Center for Energy Research and Training (CERT) in Ahmadu Bello University, Zaria. Radon concentrations for borehole water collected from 10 locations in Lagos State range between 51.78 Bq/L and 118.88 Bq/L, while those obtained from 10 selected locations in Ogun State range between 12.92 Bq/L and 110.26 Bq/L. The recorded mean values of radon concentrations obtained in this study for the borehole water in the two States were found to be above the world average Maximum Contamination Level (MCL) of 10 Bq/L set by the World Health Organization and the MCL of 11.1 Bq/L set by the United States Environmental Protection Agency (USEPA).